2017
DOI: 10.1002/ajoc.201700464
|View full text |Cite
|
Sign up to set email alerts
|

Nickel‐Catalyzed C−N Cross‐Coupling of Primary Imines with Subsequent In Situ [2+2] Cycloaddition or Alkylation

Abstract: Herein, we report an ew method for the CÀN cross-coupling of primaryi mines by using an inexpensive air-stable nickel catalyst. This procedure allows for as ubsequent in situ reaction with moisture-sensitive reagents. In this study,w ea lso report secondary [2+ +2] cycloaddition and alkylation reactions. Ad iverse range of substrates were explored to highlight the usefulness of this combinationo fr eactions.T he reactionp roducts from the cycloaddition pathway,t hrough aS taudingerr eaction, have potentiala pp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…In the past few years, our group has introduced homoleptic nickel(0) phosphite precatalysts as an easy to handle, stable alternative to using Ni­(COD) 2 . We have shown that these catalysts, in combination with chelating phosphine ligands (BINAP, dppf, Xantphos), provide active catalyst species that can be successfully applied to both C–S, and C–N, cross-coupling reactions. Other groups have also reported the effectiveness of nickel phosphine-phosphite or nickel phosphite complexes as catalysts. One limitation that we have noticed though is that these nickel diphosphine-phosphite or homoleptic nickel phosphite systems were sluggish as catalysts when used in some C–C bond forming reactions such as the Suzuki–Miyaura cross-coupling.…”
Section: Introductionmentioning
confidence: 92%
“…In the past few years, our group has introduced homoleptic nickel(0) phosphite precatalysts as an easy to handle, stable alternative to using Ni­(COD) 2 . We have shown that these catalysts, in combination with chelating phosphine ligands (BINAP, dppf, Xantphos), provide active catalyst species that can be successfully applied to both C–S, and C–N, cross-coupling reactions. Other groups have also reported the effectiveness of nickel phosphine-phosphite or nickel phosphite complexes as catalysts. One limitation that we have noticed though is that these nickel diphosphine-phosphite or homoleptic nickel phosphite systems were sluggish as catalysts when used in some C–C bond forming reactions such as the Suzuki–Miyaura cross-coupling.…”
Section: Introductionmentioning
confidence: 92%
“…Benzophenone imine, one of the most frequently used N -unsubstituted ketimines, is a well-established ammonia equivalent in Buchwald–Hartwig amination reactions. It is also an important synthetic intermediate, especially for the synthesis of glycine Schiff base, one of the most well-known starting materials for the synthesis of non-natural amino acid derivatives and related N -substituted ketimine derivatives . Benzophenone imine was also recently applied as a substrate for catalytic C–H functionalization reactions .…”
Section: Introductionmentioning
confidence: 99%